Perancangan Aplikasi Istilah Olahraga Berbasis Mobile dengan Penerapan Algoritma Apostolico-Giancarlo - Frans Yus Mori Silitonga (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
In this era of globalization, it is very necessary to have an information system that is fast and ready to use due to increasingly sophisticated human civilization and humans themselves are required to be able to adapt to these developments. Especially in the development of sports in information technology. The application design process carried out is still difficult to find the meaning of certain sports terms in sports. In order to overcome this problem, the author applies the apostolico-giancarlo algorithm to the application of mobile-based sports terms that can facilitate the information search process, compared to those who still have to search for books which require a relatively long time in searching for the meaning of sport. With the program design that has been made by the author for the general public, especially sportsmen, it is hoped that it can help in the process of finding information. The program in the form of Eclipse Juno consists of several searching, biodata, and closing